Enhancing feedback mechanisms in medical education: insights from clinical instructors in a Taiwanese medical center - Chin-Wen Liao; Chun-Nan Cheng; Wei-Sho Ho; Wei-Lun Huang; Yi-Jung Tsai (BMC Medical Education)
Abstract Objective This study aimed to evaluate clinical instructors’ agreement with and the effective implementation of the Objective Structured Clinical Examination (OSCE) in a medical center in Taiwan. Methods Clinical instructors qualified as examiners at the designated medical center were surveyed using a stratified random sampling technique. A total of 287 valid responses out of 350 questionnaires distributed were collected, yielding an 82% response rate. Descriptive statistics, independent sample t-tests, one-way ANOVA, and Pearson correlation analysis were employed for data analysis. Results The findings indicated that clinical instructors generally supported and demonstrated proficiency in the OSCE. Moreover, those who had participated in more scoring activities and received faculty training in the past three years showed stronger alignment with the OSCE and greater effectiveness in its implementation. A moderate to high positive correlation was found between instructors’ endorsement of the OSCE and their successful execution of it. Conclusions The results underscore the importance of clinical instructors’ endorsement and proficiency in OSCE implementation. These findings hold significance for medical education administrators, clinical instructors, and future research endeavors in medical education, aiming to enhance instructional quality.